Factors affecting the retention of adult students within an indigenous tertiary institution - Wiseley, Adelle Dyane (Curtin University, 2009)
This study sought to identify influences on the retention of Māori students, and adult students in general within Te Wānanga o Aotearoa. Te Wānanga o Aotearoa is a Māori-led tertiary institution in New Zealand. A mixed method research design was employed and data were collected by qualitative methods (focus group) and quantitative methods (72-item questionnaire). Inductive and deductive analytic techniques were employed including Rasch Rating Scale model estimations (Andrich, 1978). Seven retention variables were identified. These were student retention attitudes and behaviours, kaiako (teacher) characteristics, whānau (family) features, integration processes and institutional culture, employment and financial situation, student motivation, and pre-enrolment and induction processes. The variables were qualified and quantified by plotting item difficulty measures and person ability measures on the same scale. Additionally, associations between variables were examined by a multiple regression analysis and analysis of variance. Student retention attitudes and behaviours were shown to be positively associated with kaiako (teacher) characteristics and student motivation. Also the ethnicity of the student (Māori or non-Māori) was shown to weakly account for variance in integration processes and institutional culture.After highlighting the key factors affecting the retention of students at Te Wānanga o Aotearoa, four propositions were made regarding ways to improve their retention. These were: Kaiako (teachers) need retention related training; External motivation for kaiako (teachers) will improve student retention; Improved student retention requires a change in institutional culture; The measurement of retention attitudes and behaviours could provide data essential for increasing retention. The study has led the way for future research in the following areas: Using the student voice to provide a grounded view of retention; Researching the area of kaiako (teachers) and pedagogy with regards to their ability to positively affect retention; Researching the role of whānau (family) features to effectively configure support programmes to positively affect retention; Identifying significant factors that contribute to adult students feelings of pressure, negatively affecting their retention.